Website Development for Environmental Pollution Topics Based on Inquiry Learning Model - Iyan Sopian; Bibin Rubini; Indarini Dwi Pursitasari (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Various online media platforms, such as Google Classroom, Zoom, and WhatsApp, have been widely utilized to optimize teaching and learning activities. However, these platforms have not yet integrated inquiry-based learning into the science education process, resulting in limited engagement of students' critical thinking skills. Consequently, there is a need to develop an Inquiry-Based Environmental Pollution Learning Website (WPPLI) as a learning medium to address students' needs for more effective learning. This study aims to: (1) determine the feasibility of the WPPLI as an educational tool, and (2) analyze teachers' and students' responses to the WPPLI. This research employs a Research and Development (R&D) methodology, utilizing the ADDIE (Analyze, Design, Develop, Implement, Evaluate) design model. Data were collected through media and content expert validation forms, as well as teacher and student response questionnaires. The results indicate that the WPPLI has been deemed suitable as a learning medium based on validation by media and content experts, with respective scores of 94.02% and 97.77%, both categorized as "Highly Suitable." Field testing of the WPPLI revealed average responses of 96.83% from teachers and 81.55% from students, both falling within the "Excellent" category